ECONOMIC COMPLEXITY OF INTERNATIONAL TRADE BETWEEN UKRAINE AND EU COUNTRIES IN THE CONDITIONS OF BILATERAL LIBERALIZATION OF CUSTOMS REGULATION - Berenda , S.V.; Grygorova-Berenda , L.I. (The actual problems of regional economy development, 2025)
Purpose. The purpose of this article is to identify changes in the structural complexity of international trade between Ukraine and European Union (EU) countries under the conditions of customs liberalization, particularly within the framework of the Deep and Comprehensive Free Trade Area (DCFTA), based on the calculation of the Economic Complexity Index (ECI). The research aims to reveal qualitative transformations in trade flows between Ukraine and its key partners as a result of integration processes. Methods. The study applies the spectral analysis method to compute the Economic Complexity Index (ECI) based on matrices of Revealed Comparative Advantages (RCA) for the period 2014–2024. The analysis includes 27 EU countries, the United Kingdom, as well as China, the United States, India, Switzerland, and other trade partners. Additional indicators such as export diversification, product ubiquity, and the Method of Reflections are used to capture structural trade dynamics. Scientific novelty. The research introduces new derived indicators — ΔECI (the gap between national and global complexity levels) and the Index of Growth in Complexity (IGS), which allow for a comprehensive assessment of the qualitative evolution of trade. An analytical grouping of countries by ΔECI level was carried out to identify partners that facilitate or hinder Ukraine's integration into markets for complex products. Results. It is established that Ukraine’s trade with EU countries shows a higher level of economic complexity compared to global and regional averages, especially following the full implementation of the DCFTA in 2017. The highest ECI values are recorded in trade with Germany, France, and the United Kingdom. In contrast, trade with Asian and Middle Eastern countries exhibits lower complexity indicators. Conclusions. The findings confirm the hypothesis that customs liberalization facilitates structural shifts toward higher value-added products. The Economic Complexity Index proves to be an effective tool for evaluating Ukraine’s integration into global and regional value chains (GVCs) and justifies the relevance of further institutional convergence with the EU, including the potential formation of a customs union.